2000
DOI: 10.1046/j.1468-3083.2000.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies in melanoma patients in Thuringia

Abstract: Second malignancies were seen in 11.0% of melanoma patients. Most important are second skin tumours such as second melanomas and BCC, recommending follow-up by the dermatologist. In a group of patients with regular follow-up examinations, no negative impact of second tumours (BCC, melanoma, breast cancer) on overall survival could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Previous studies found incidences ranging from 2.0% to 8.0% [13, 15, 16, 5254]. In accordance with previous studies, our data indicate that most subsequent CM occur within the first years after the initial diagnosis [13, 17, 53, 54].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies found incidences ranging from 2.0% to 8.0% [13, 15, 16, 5254]. In accordance with previous studies, our data indicate that most subsequent CM occur within the first years after the initial diagnosis [13, 17, 53, 54].…”
Section: Discussionsupporting
confidence: 91%
“…38 In the present study, the finding of 27,7% of the patients with a history of non-melanoma skin cancer is higher than that found in the literature. 39,40 One possible explanation would be the chronic exposure to the sun, which may also explain the elevated frequency of CM on the head and neck, even though this feature has not been evaluated by this study.…”
Section: Discussionmentioning
confidence: 87%
“…2 Because case fatality has declined in recent decades, 3 more individuals with a CM diagnosis will survive to develop a second primary malignancy (SPM). Patients with melanoma have been reported previously to have increased relative risk for particular SPMsenamely, second primary melanomas (standardized incidence ratio [SIR] range, 4.7-33.8), 4-7 nonmelanoma skin cancer (SIR range, 3.10-4.40), 4,8,9 lymphoma (SIR range, 1.42-16.1), 4,10,11 and cancers of the breast (SIR range, 1.10-6.6), 4,[12][13][14] thyroid (SIR range, 2.1-3.6), 4,15 pancreas (SIR range 0.6-1.76), 4,16-18 bladder (SIR range, 0.9-3.30), 4,19 prostate (SIR range, 1.50-2.10), 4,8,13,19 central nervous system (SIR range, 1.1-1.57, 4,20 and gastrointestinal tract (SIR range, 1.1-1.33). 4,21 However, reported SIRs have not been consistent across studies.…”
mentioning
confidence: 99%